Panorama de pesquisa sobre gestão da hotelaria hospitalar e a comparação de prestação de serviços de lavanderia hospitalar do HC-UFU - Diniz, Allan Marcio Oliveira (2019)
The present work has as its main theme the hospital hospitality management and the services performed by it in order to demonstrate its importance as a support service in the hospital context, especially the laundry service. The dissertation is composed of two articles, the first of which was to analyze Brazilian scientific production in the hospital hospitality sector between 2013 and 2018, through a bibliometric review. On the laws of bibliometrics, it is noted that in the present study Lotka's Law was not confirmed, the Bradford Act was not confirmed and Zipf's Law was confirmed. There are several areas of knowledge that deal with hotel management with different approaches such as: nursing, medicine, nutrition, psychology, administration, economics, education, working on topics such as hospital humanization, hospital transportation, hospital laundry, sanitation and hospital and hotel cleaning hospital itself. It was possible to conclude that, despite the development of the theme, there are gaps, mainly, regarding the management of hospital hotels in public hospitals. Regarding the second article, the purpose of the research was to analyze the contracting models of the hospital laundry service of the HC-UFU, from the year of 2010 when the outsourcing of the service was started, in order to compare the contracting models for the control of costs and improvement in the care of HC-UFU patients and professionals, specifically regarding the availability of hospital lay-out under appropriate conditions of use. The research used the technical procedure of a single case study, the HC-UFU laundry being the locus of the study. The data collection was done through documentary research in contracts, memoranda, offices, terms of reference among other documents. In the course of the work, the three contract modalities of the garment processing service performed at the HC-UFU from 2010 to 2018 were presented, specifically addressing the negative aspects of each one. Later, it was concluded that it is indispensable to implement a new model of which was suggested by the author as a way to contemplate the needs of the hospital without incurring the same mistakes made in other models and always giving a good value for money. Finally, the suggestion of this new model represents the technological product of this dissertation.